Penerapan Media Flash card Bermuatan Tema Hewan untuk Meningkatkan Pengenalan Huruf dan Suku Kata Berawalan “L” Siswa Kelas I Sekolah Dasar - Pristia Eka Yuliana; Novialita Angga Wiratama; sri Cacik (Tunas Nusantara, 2026)
The background of this study is the low level of mastery of letters particularly syllables beginning with L among students in Year 1 at SDN Sidorejo 1 Tuban. Two main objectives were formulated: to describe the implementation of animal-themed flash cards and to examine their impact on students' ability to recognise letters. A Classroom Action Research (PTK) design with Kemmis and McTaggart's model was implemented, covering the planning, execution, observation, and reflection stages. The participants consisted of 20 first grade students (12 boys and 8 girls). Data was collected through written tests, observations, interviews, and documentation. The results showed a significant increase: the class average in Cycle I was 72.5 with a class completion rate of 40%, and in Cycle II it increased to 82.25 with a class completion rate of 95%. These results demonstrate that flash cards with animal themes are effective in creating an active, enjoyable and meaningful learning environment in lower-level classes.